Indirect Effect of Organizational Climate and Work Discipline on Employee Performance PT. Karya Lima Sahabat with Competence as a Mediator - Wahyuddin Latunreng; Eric Hermawan; Resista Vikaliana (Universitas Mercu Buana, 2023)
For the purposes of investigating the performance of employees of PT. This time, the work of Lima Sahabat uses the independent variables of organizational climate, work discipline and competence. The investigation was carried out based on the indirect effect of organizational climate and work discipline on the performance of employees of PT. Karya Lima Sahabat with competence as a mediator. This indirect effect can be determined by determining the direct effect of organizational climate, work discipline and competence partially on the performance of employees of PT. Karya Lima Sahabat. The direct influence of organizational climate and work discipline partially on competence. The method used in this study is a quantitative method with a descriptive research type that describes the phenomenon being studied. For this purpose, questionnaires were distributed to 82 respondents who were employees of PT. Karya Lima Sahabat. Since the population is less than 100, a full sample is taken which is the same as the population. The regression equation work was carried out after the research data was tested with validity, reliability, normality, multicollinearity and heteroscedasticity tests. For simple regression the significant and positive effect is determined by the t-test, if tcount>ttable the regression equation is positive and significant. Whereas for multiple regression it is done by F-test, if Fcount>Ftable the multiple regression equation is significant and positive. The results of the study found that for all direct and indirect effects were significant and positive. The influence of organizational climate variables, work discipline and competence partially on the performance of employees of PT. Karya Lima Sahabat in percent is 23.3%, 25.7% and 27.0%. This effect value is true because all Fcount>Ftable(24,332, 27,715 and 29,604 > 3,57). The effect of organizational climate and work discipline partially on competency in percent is 35.3% and 63.7% of this effect is true because all Fcount>Ftable (43.552 and 140.415> 3.57).